1995
DOI: 10.1016/s0006-3495(95)80076-7
|View full text |Cite
|
Sign up to set email alerts
|

Charge displacement in bacteriorhodopsin during the forward and reverse bR-K phototransition

Abstract: Dried oriented purple membrane samples of Halobacterium salinarium were excited by 150 fs laser pulses of 620 nm with a 7 kHz repetition rate. An unusual complex picosecond electric response signal consisting of a positive and a negative peak was detected by a sampling oscilloscope. The ratio of the two peaks was changed by 1) reducing the repetition rate, 2) varying the intensity of the excitation beam, and 3) applying background illumination by light of 647 nm or 511 nm. All of these features can be explaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
0
12
0
2
Order By: Relevance
“…Direct measurements of this charge separation process by using photovoltaic techniques have been performed (17)(18)(19). However, the intrinsic temporal resolution of these techniques is limited to several picoseconds; i.e., slower than the Ϸ500-fs (4, 20) isomerization process.…”
mentioning
confidence: 99%
“…Direct measurements of this charge separation process by using photovoltaic techniques have been performed (17)(18)(19). However, the intrinsic temporal resolution of these techniques is limited to several picoseconds; i.e., slower than the Ϸ500-fs (4, 20) isomerization process.…”
mentioning
confidence: 99%
“…Such data were obtained for purple membranes and apomem branes after the application of an electric field with E = 2 ⋅ 10 5 -3 ⋅ 10 6 V/m 2 [55][56][57][58]. Optoelectric mea surements in a suspension of the purple membranes demonstrated that a strong electric field resulted in a change in the BR optical properties at the wavelength of the chromophore absorption (λ = 565 nm) and in the area of 400 nm.…”
Section: Electro Activation and Photo Activation Of Opsinmentioning
confidence: 84%
“…The next step of the photocycle is the formation of the K intermediate, which can be described by exponential kinetics with a time constant ( 2 ) of 3 and 6 ps for the native and the acid blue form, respectively (31,32). If these kinetics are associated with a jump of protons from one metastable position to another, as indicated by previous direct electric measurements (6)(7)(8), on a macroscopic scale this corresponds to an accelerated proton current, leading to terahertz emission. This component of the emission can be associated with the slow phase observed in our signal.…”
Section: Model Ii: Intramolecular Electron Transfer (Resonant Opticalmentioning
confidence: 90%
“…The most direct way to study these processes is to measure the electrical signal arising from the intramolecular dipole moment change of oriented samples (5)(6)(7)(8). Previous studies of this kind were carried out from the ''physiological'' time domain of microseconds to seconds (5) down to the range of several picoseconds (6)(7)(8).…”
mentioning
confidence: 99%
See 1 more Smart Citation